A Holistic Model for Disciplinary Professional Development-Overcoming the Disciplinary Barriers to Implementing ICT in Teaching - Alisa Amir (MDPI AG, 2023)
What helps teachers overcome technological barriers to Information and Communications Technology (ICT) implementation in their subject domains? Can a disciplinary professional development model help reduce these disciplinary barriers? To answer these questions, this mixed-methods case study examines the change in digital ICT implementation and its barriers among secondary school first language teachers after the utilization of a holistic model for disciplinary professional development (language, science, etc.). Ninety-two first language teachers participated in a professional development program that included a unique instructor profile, theoretical and practical training, technical support, and ongoing individual and school-wide didactic and pedagogical support. The teachers' experiences and changes in their personal general experience during their professional development were then assessed via interviews and open-ended questionnaires. The findings indicate that the unique professional development model largely removed the teachers' disciplinary barriers. Specifically, during their professional development, the teachers changed their perceptions of the purposes of ICT in first language teaching in general and teaching writing in particular, indicating that they realized that ICT promotes their discipline and is not merely a tool for lesson diversification or intrigue. Furthermore, they recognized that ICT is not an option but an integral part of teaching in the 21st century.